2000
DOI: 10.1103/physrevb.61.8667
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle resonant states induced by a unitary impurity in ad-wave superconductor

Abstract: The quasiparticle resonant states around a single nonmagnetic impurity with unitary scattering in a d-wave superconductor is studied by solving the Bogoliubov-de Gennes equations based on a t-J model. Both the spatial variation of the order parameter and the local density of states (LDOS) around the impurity have been investigated. We find: (i) A particle-hole symmetric system has a single symmetric zero-energy peak in the LDOS regardless of the size of the superconducting coherence length ξ0; (ii) For the par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
4
30
2
Order By: Relevance
“…3(b), the ratio between the ZBCP height to that of the gap-structure varies spatially. This may be due to nano-faceting of the (110) surface 11 or to the effect of local roughness or disorder 19,29,30 .…”
Section: Morphology and Local Tunneling Spectra Correlationmentioning
confidence: 99%
“…3(b), the ratio between the ZBCP height to that of the gap-structure varies spatially. This may be due to nano-faceting of the (110) surface 11 or to the effect of local roughness or disorder 19,29,30 .…”
Section: Morphology and Local Tunneling Spectra Correlationmentioning
confidence: 99%
“…In the presence of a single impurity in the unitary scattering limit, an earlier study has shown [20] that the order parameter is strongly suppressed near the impurity site on a scale of a few lattice constants. To take into account this effect, the order parameters on bonds connecting with the strong impurity sites are taken as zero.…”
mentioning
confidence: 99%
“…Especially, the experiment by Pan et al [9] on the observation of quasiparticle resonant states has a high spatial and energy resolution and the identity of impurity atoms is known in a controlled way. Very interestingly, the imaging of the effect of a single zinc (Zn) impurity atom showed the strongest intensity of the LDOS at resonance directly on the Zn atom, which is opposite to the earlier theories [3][4][5][6]. In our previous work [10], we explained the novel pattern of the tunneling conductance in terms of the blocking effect of the BiO and SrO layers which exist between the tunneling tip and the CuO 2 layer being probed.…”
mentioning
confidence: 93%
“…As an important signature of the sign change of d-wave order parameter (OP), Balatsky, Salkola and co-workers [3,4], based on the T-matrix approximation, theoretically predicted that a strong atomic-like nonmagnetic impurity can induce a virtual bound state. Later studies [5,6] showed that the resonant state would show up in the local density of states (LDOS), which could be measured by the local differential tunneling conductance. Recent scanning tunneling spectroscopy measured on high-T c superconductor Bi 2 Sr 2 CaCu 2 O 8+δ (BSCCO) with individual atomicscale defects [7] or strong impurities [8,9], has provided strong evidence for the existence of low-energy quasibound states.…”
mentioning
confidence: 99%